Shared decision making supported by patient decision aids for prostate cancer screening and treatment - Michael J. Barry (Psicooncologia, 2010)
Prostate cancer is an important problem among aging men in developed countries. Decisions about prostate cancer screening and treatment are characterized by multiple reasonable options and appear to be “close calls”, where the personal preferences of patients are important. Shared decisionmaking between patient and clinician is increasingly recognized as an ideal model for such “preference sensitive” choices involving screening, diagnosis, and therapy. Many randomized trials of decision aids for prostate cancer screening have consistently shown improvements in decision quality as well as lower interest in and uptake of PSA testing when patients are well informed. In contrast, more research is needed on the effect of decision aids on prostate cancer treatment decisions. However, given the evidence of effectiveness available at present, research is most urgently needed on how to routinely implement patient decision aids for PSA screening, as well as other fateful decisions including prostate cancer treatment, in clinical practice.